Neuropsychological assessment of Romanian burning mouth syndrome patients: stress, depression, sleep disturbance, and verbal fluency impairments - Dugan, Cosmin; Popescu, Bogdan Ovidiu; Țovaru, Serban; Părlătescu, Ioanina; Musat, Ioana Andreea; Dobre, Maria; Ribigan, Athena Cristina; Milanesi, Elena (Frontiers in Psychology, 2023)
Burning Mouth Syndrome (BMS) is a chronic condition characterized by a burning sensation in the oral mucosa, lasting more than 2 hours daily for more than 3 months, without clinical and/or laboratory evidence. BMS is often comorbid with mood, and psychiatric disorders, and a complex pathophysiology and interaction between impairments in nociceptive processing and psychologic function is occurring. In this work, we aimed to define the neuropsychological profile specific for BMS patients for a better management of this complex disease. We conducted a case–control study comparing 120 BMS patients and 110 non-BMS individuals (CTRL). Sociodemographic data and lifestyle habits, were collected, along with data regarding quality of life (SF-36 scale), stress (PSS), depression and anxiety (MADRS and HADS scales), sleep quality (PSQI scale), and cognitive functions (MoCA, SVF and PVF tests). The statistical analysis revealed a lower general quality of life (p < 0.001), worse sleep quality (p < 0.001) in BMS patients than CTRL. The BMS patients also displayed a higher prevalence of mild depressive symptoms than CTRL applying the MADRS (p < 0.001) and HADS-Depression scales (p = 0.001), whereas no differences in anxiety symptoms were found between the two groups (p = 0.174). Moreover, reduced scores semantic and phonemic verbal fluency tests (p < 0.05) were found, but no change in cognition was observed through MoCA (p = 0.551). Our results highlight that synergy between dentistry and neuropsychiatric assessment is essential for a successful management of BMS.